Design Monthly Report Application in The Sub Division of Evaluation Planning and Reporting of The Department of Education and Culture of Bengkulu Province - Andry Ardian; Leni Natalia Zulita; Reno Supradi (Jurnal Komputer, Informasi dan Teknologi, 2021)
In the process of managing monthly report data activities in the Environment Department of Education and Culture of Bengkulu Province does not have a special application that can help process data and store data automatically. This makes it difficult and vulnerable to miscalculation when wanting to make a recap of monthly reports, considering the Department of Education and Culture is one of the agencies with the largest number of activities in the government of Bengkulu Province, therefore it takes an application that can help process data and can store data from the processed. therefore, an application is needed that can help process data and can store data from the processed. therefore, create a Monthly Report Application Using Visual Basic Applications. Net 2010 and SQL 2008 database to facilitate the input of monthly reports at the Department of Education and Culture of Bengkulu Province